Pengaruh Budaya Organisasi, Gaya Kepemimpinan, dan Pelatihan Terhadap Kinerja Karyawan Pada Kantor Dinas Tenaga Kerja Dan Transmigrasi Provinsi D.I Yogyakarta - Ika Aprilia Cahyani; Jajuk Herawati; Epsilandri Septyarini (Universitas Batanghari, 2021)
Employee performance affects how much a person contributes to the organization. A good organizational culture can improve employee performance in the organization. The leadership style adopted by a leader has a major role in achieving a good work environment in the organization. Training is a process of self-development by employees so that they can work more skillfully, increase the knowledge and expertise of an employee. The purpose of this study was to determine the effect of organizational culture, leadership style and training on employee performance at the Department of Manpower and Transmigration of the Province of D.I Yogyakarta. Respondents in this study amounted to 75 employees at the Department of Manpower and Transmigration of D.I Yogyakarta Province. The research method used this time using quantitative methods. While the data analysis methods used include validity test, reliability test, multiple linear regression test, and classical assumption test. The results of this study indicate that organizational culture has a significant effect on employee performance, leadership style has no significant effect on employee performance, training has a significant effect on employee performance, and organizational culture, leadership style, and training have a simultaneous effect on employee performance.